A NEW WHITE DWARF IN THE TAURUS DARK CLOUD - LUYTEN, WJ; HARO, G (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1967)
We present coordinates and finding chart of a previously unidentified white dwarf of magnitude 14.3 projected against dark clouds. We have found no variability and no emission lines for the star. Its colors are approximately B-V = -0.1 and U-B= -0.5. Beca
BOL OBS TONAN TACUB
Keywords: NEW, DWARF, TAURUS DARK, CLOUD; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS VARIABLES